Investigation of Impregnation Approach of Zinc Oxide Nano-Dispersions for Potential UV Stabilization in Abies alba and Fagus sylvatica - Lukas Sommerauer; Alexander Petutschnigg; Thomas Schnabel (Compounds, 2023)
As biological material, wood is distinctly affected by to various environmental influences during use. Reductions in durability can come from ultraviolet (UV) radiation, insects, fungi, and microorganisms in both exterior and interior applications. Wood can be easily protected from living organisms via the control of moisture content; however, UV radiation is not so easily managed. Wood components subject to this degradation are damaged and decomposed at a molecular level leading to deterioration of surface quality, especially in visible application areas. A potential remedy to this is using the UV-stabilizing properties of zinc oxide nanoparticles. Zinc oxide nano-dispersions based on propylene glycol (PG) were introduced into the microscopic structure of fir (Abies alba) and beech (Fagus sylvatica) wood by whole-cell impregnation to overcome problems associated with surface coatings. In this work the material uptake of ZnO nano-dispersions in concentrations of 1%, 2%, and 3% w/v were investigated and their effect on the stability of the optical appearance to UV exposure in short-term weathering were evaluated. Untreated reference samples showed significant photo-yellowing. A 1% w/v ZnO dispersion significantly increased the UV stability of treated surfaces. It was found that the uptake of the nano-dispersions was independent of the proportion of ZnO, and that the impregnating agents penetrated fir wood (about 200%) stronger than beech wood (about 70%). Already, a 2% w/v ZnO nano-dispersion led to a saturation of ZnO in the cell structure of the treated wood, for fir as well as beech, and no further ZnO uptake was achieved with 3% w/v nano-dispersions. Scanning electron microscopy shows an agglomeration of ZnO-NP in the cellular pathways impacting penetration, reducing leachability at higher concentrations.